ACCIDENTAL INHALATIONAL POISONING BY MULTIPLE PESTICIDES OF ORGANOPHOSPHORUS GROUP IN AN AGED PERSON; AN UNCOMMON OCCURRENCE (Journal of Forensic Medicine & Toxicology, 2013)
Acute pesticide poisoning is a global public health problem and accounts for thousands of deaths worldwide every year. Most of fatalities occur due to exposure to (OP), organochlorines and aluminium phosphide. Among them, organophosphates OP poisoning is common-est in India. OP compounds account for a significant pesticide related illness and death in developing countries, including India, which is a predominantly agrarian country with large rural population and pesticides are extensively used in farming. Acute OP poisoning is a medical emergency with fatal outcome if not managed meticulously. It is typically suicidal, and very uncommonly accidental or homicidal in nature. Its most common presentation is deliberate self ingestion in young population (20 -30 yrs) for suicidal purpose and quite uncommon in aged people more than 50 yrs. In this communication we report a case of a 55 yrs old farmer who had accidental inhalational exposure of multiple OP pesticides during routine spraying in fields, despite of taking preventive measures. He was admitted to causality, showed a good clinical response to treatment and had a successful recovery.
Keywords: Organophosphate; Pesticide; Accidental; Inhalational; Poisoning